Cryptococcal Meningitis Screening and Community-based Early Adherence Support in People With Advanced Human Immunodeficiency Virus Infection Starting Antiretroviral Therapy in Tanzania and Zambia: A Cost-effectiveness Analysis. (31st May 2019) - Kimaro, Godfather Dickson; Guinness, Lorna; Shiri, Tinevimbo; Kivuyo, Sokoine; Chanda, Duncan; Bottomley, Christian; Chen, Tao; Kahwa, Amos; Hawkins, Neil; Mwaba, Peter; Mfinanga, Sayoki Godfrey; Harrison, Thomas S; et al.
Abstract: Background: A randomized trial demonstrated that among people living with late-stage human immunodeficiency virus (HIV) infection initiating antiretroviral therapy, screening serum for cryptococcal antigen (CrAg) combined with adherence support reduced all-cause mortality by 28%, compared with standard clinic-based care. Here, we present the cost-effectiveness. Methods: HIV-infected adults with CD4 count <200 cells/μL were randomized to either CrAg screening plus 4 weekly home visits to provide adherence support or to standard clinic-based care in Dar es Salaam and Lusaka. The primary economic outcome was health service care cost per life-year saved as the incremental cost-effectiveness ratio (ICER), based on 2017 US dollars. We used nonparametric bootstrapping to assess uncertainties and univariate deterministic sensitivity analysis to examine the impact of individual parameters on the ICER. Results: Among the intervention and standard arms, 1001 and 998 participants, respectively, were enrolled. The annual mean cost per participant in the intervention arm was US$339 (95% confidence interval [CI], $331–$347), resulting in an incremental cost of the intervention of US$77 (95% CI, $66–$88). The incremental cost was similar when analysis was restricted to persons with CD4 count <100 cells/μL. The ICER for the intervention vs standard care, per life-year saved, was US$70 (95% CI, $43–$211) for all participants with CD4 count up to 200 cells/μL and US$91 (95% CI, $49–$443) among those with CD4 counts <100 cells /μL. Cost-effectveness was most sensitive to mortality estimates. Conclusions: Screening for cryptococcal antigen combined with a short period of adherence support, is cost-effective in resource-limited settings. Abstract : In a large phase 3 randomized controlled trial among persons presenting with late-stage HIV infection, we showed that cryptococcal meningitis screening and community-based early adherence support was a highly cost-effective strategy in reducing all-cause mortality.